Enhancing IPPEKas Digital Transformation for Effective Circular Economy Management - Lis Saumi Ramdhani; Yusti Farlina; Andi Riyanto; Mochamad Wahyudi; Lise Pujiastuti; Rizal Amegia Saputra (Computer Science (CO-SCIENCE), 2026)
Achieving successful digital transformation in community-based circular economy organizations requires more than the deployment of digital technologies. Sustainable organizational outcomes depend on the effective interaction of technological capability, organizational readiness, and user engagement. This study evaluates the effectiveness of the IPPEKas information system by integrating the DeLone and McLean Information Systems Success Model, the Human–Organization–Technology Fit (HOT-Fit) framework, and System Usability into a unified analytical model. Data were collected from 100 active IPPEKas users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical findings reveal that Information Quality, Organizational Support, and System Usability significantly enhance Net Benefits, whereas System Quality contributes indirectly through its positive influence on System Usability. These findings indicate that organizational value is created primarily through high-quality information and effective user interaction rather than through technical excellence alone. The proposed integrated framework advances information systems success research by combining technological, human, and organizational dimensions into a comprehensive evaluation model. From a practical perspective, the findings provide actionable recommendations for strengthening information governance, encouraging sustained system utilization, and improving organizational support to maximize the long-term value of digital transformation in community-based circular economy organizations.